THE PRODUCTION OF PELLETS IN SERBIA: A STUDY FROM COMPANY C - Ljiljana, Kontić; Petrović, Pero; Kontić, Jovan (Economics of Agriculture, 2013)
This paper examines the issue of renewable energy through production of pellet as one part of biomass. The research setting consisted of a domestic company that operates in Serbia. The biomass as a potential energy source is well-explored issue by scientists and practioners in developed countries. There are few studies of using biomass in developing countries such as Serbia. The purpose of this study is to analyze feasibility of producing pellets in selected company in Serbia. This paper contributes to the existing literature by assessing production pellet in a company that operates in transition environment. The findings have significant implications for practitioners attempting to manage projects in the domain renewable energy. Furthermore, the study provides the example of good practice for other entrepreneurs in Serbia.